Review of clinical non-medico-legal autopsy: a descriptive study in 747 patients (2018)
Background: Autopsies have been an essential element to healthcare professionals’ training, as well as to research processes, education, and public health. In spite of the decline of clinical autopsy rate after the Joint Commission on the Accreditation of Hospitals eliminated the minimum autopsy rate required for accrediting hospitals, in Colombia, South America, we have seen that this practice has been reinitiated and our institution has performed more than 200 autopsies per year. Objective: To describe the main causes of death among individuals to whom a clinical autopsy was practiced at a general hospital in Bogotá, Colombia. Methods: A descriptive study of autopsy reports during the period between January 2012 and June 2015 was conducted. Results: The study included 747 autopsies of which 58.2% were performed in males. The majority of deaths occurred among the 41 to 64 years (mean 32.53, SD 28.53) age group. The leading cause of death observed in young adults and middle-aged adults (18 to 64 years) was cardiac arrest (58.5%) associated with acute myocardial infarction, cardiomyopathies, or cardiovascular abnormalities, followed by respiratory conditions (42.6%) and cardiac sudden death as the second cause of death in young adults. Conclusions: Studies based on clinical autopsies allow precise knowledge on the main underlying causes of death in a population, as well as, enable ideas based on key data obtained to be used in the development of cardiovascular prevention strategies for the different age groups thus preventing fatal outcomes in young adults who are the active working, productive population in society.